Effect of fiber volume ratio on flexural behavior of RC beam with novel HFRP rebar and steel rebar. (September 2022) - Qin, Weihong; Fernand, Muhirwa; Yang, Zhen-Jun; Georges, Irankunda; Zakari, M. Djibo
Highlights: The effect of fiber volume ratio on mechanical properties of HFRB bar is investigated. The idea of improving flexural load and enhance ductility of HFRP-RC beam is suggested. The distinctive flexural mechanism of specimens with high hybrid FRP ratio is experimentally found. FEM analysis of the flexural behavior of concrete beams with hybrid FRP and steel rebar is simulated. Abstract: In the experiment conducted, a total number of ten reinforced concrete (RC) beams were analyzed to investigate the flexural performance of concrete beams reinforced with locally fabricated hybrid fiber-reinforced polymer (HFRP) bars and steel bars. The yield load and post-yield stiffness of specimens were the main mechanical properties variables that have been carried out during specimens design. Furthermore, the effect of the fiber volume ratio in the HFRP rebar and the reinforcement ratios on the flexural behavior of specimens has been studied. The experimental results show a significant improvement in the flexural load capacity due to the increases of HFRP reinforcement ratio than steel bars. The flexural capacity of beam specimens with 0.47% of HFRP reinforcement ratio and (0.24%, 0.48%, 0.71%) of steel bar, were 169kN, 198kN, and 221kN respectively, while with 0.23% HFRP bar and (0.36%, 0.6%, 0.84%) of steel ratio were 116kN, 150kN, and 138kN respectively. Further, the HFRP bar with a high volume ratio of carbon fiber improves the flexural strength, although the HFRP bar with a high volume ratio of basalt fiber enhances the ductility behavior of specimens. A finite element model (FEM) analysis was conducted using Abaqus Software. It was observed that the FEM analysis perfectly generate the results that matched with the experiment results. Conclusively, an analytical method was suggested to predict flexural strength and compared with experimental results. The analytical flexural strength was in good agreement with the experimental results.